2012
DOI: 10.5209/rev_sjop.2012.v15.n3.39397
|View full text |Cite
|
Sign up to set email alerts
|

Motivational and Emotional Profiles in University Undergraduates: a Self-Determination Theory Perspective

Abstract: Previous research has focused on specific forms of self-determined motivation or discrete class-related emotions, but few studies have simultaneously examined both constructs. The aim of this study on 472 undergraduates was twofold: to perform cluster analysis to identify homogeneous groups of motivation in the sample; and to determine the profile of each cluster for emotions and academic achievement. Cluster analysis configured four groups in terms of motivation: controlled, autonomous, both high, and both lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 42 publications
4
28
1
9
Order By: Relevance
“…In both studies, female students reported a higher autonomous motivation compared to male students [13], [37]. The existence of the same four distinct motivational profiles was confirmed in a study of undergraduate students, and no difference in achievement was observed between motivational profile A (high autonomous motivation, low controlled motivation) and motivational profile B (students with high autonomous and high controlled motivation), suggesting that controlled motivation is not detrimental for study achievement when coupled with high levels of intrinsic motivation [38]. Although it has been suggested that an autonomous motivational profile is more likely to develop in a college or university context, which is often more autonomy supportive compared to the more controlling climate in high school context [9], [37], [39], also university programs require perseverance in some subjects that might not always be perceived as interesting.…”
Section: Introductionmentioning
confidence: 77%
“…In both studies, female students reported a higher autonomous motivation compared to male students [13], [37]. The existence of the same four distinct motivational profiles was confirmed in a study of undergraduate students, and no difference in achievement was observed between motivational profile A (high autonomous motivation, low controlled motivation) and motivational profile B (students with high autonomous and high controlled motivation), suggesting that controlled motivation is not detrimental for study achievement when coupled with high levels of intrinsic motivation [38]. Although it has been suggested that an autonomous motivational profile is more likely to develop in a college or university context, which is often more autonomy supportive compared to the more controlling climate in high school context [9], [37], [39], also university programs require perseverance in some subjects that might not always be perceived as interesting.…”
Section: Introductionmentioning
confidence: 77%
“…La respuesta de estrés en humanos ha sido ampliamente estudiada, en diferentes contextos, especialmente en el ámbito clínico y de la salud (Costarelli y Patsai, 2012;Hamdan-Mansour, Puskar, y Bandak, 2009;Gulewitsch et al, 2013;O'Donovan y Hughes, 2007;Pettit y De Barr, 2011). En el ámbito educativo, si bien se ha avanzado bastante en el conocimiento de los procesos cognitivos y metacognitivos, no se le ha prestado la atención suficiente para esclarecer con precisión los mecanismos que operan es esta respuesta, por su efecto pernicioso que puede operar en dichos procesos cognitivos y motivacionales-afectivos (de la Fuente, Zapata, Martínez-Vicente, Sander y Putwain, en prensa).…”
Section: La Respuesta De Estrés Durante El Aprendizaje Y El Rendimienunclassified
“…La decisión de iniciar estudios universitarios implica un proceso de búsqueda y selección donde los estudiantes priorizan ciertos motivos de elección de estudios que pueden responder tanto a valoraciones y motivaciones propias como a factores externos reflejados, por ejemplo, en expectativas familiares o estereotipos sociales (Abarca, Gormaz, & Leiva, 2012;Navarro Guzmán & Casero Martínez, 2012;Valle Arias et al, 2010). Las razones que manifiestan los estudiantes al momento de elegir una carrera universitaria pueden estar fundamentadas en actitudes motivacionales hacia el aprendizaje y hacia la vida profesional de carácter intrínseco, o bien tener un carácter más extrínseco (González Maura, 2004;Grouzet et al, 2005;Ryan & Deci, 2000). Por ejemplo, la elección de unos estudios por la búsqueda de recompensas externas o la proyección de ciertos resultados, tales como alcanzar el reconocimiento y prestigio profesional u obtener un empleo bien remunerado, son entendidos como motivos extrínsecos (Gámez, Marrero, & Díaz, 2008).…”
unclassified
“…En cambio, los motivos más intrínsecos estarían asociados a actividades que en sí mismas tienen una recompensa o que responden a la búsqueda de la realización personal, como el deseo de aprender o el logro de un desarrollo personal y profesional a través de los estudios universitarios (Cano Celestino, 2008). Los estudiantes, en el momento de elegir una opción de estudio superior, pueden sostener en forma simultánea una serie de razones y combinar motivos intrínsecos y extrínsecos en diversos grados (González, Paoloni, Donolo, & Rinaudo, 2012). Esto a la vez puede incidir en el posterior desarrollo de la carrera profesional, tanto en cuanto al desempeño como a la continuidad de los estudios y, posteriormente, en las habilidades de adaptación al mundo laboral (Ye, 2015).…”
unclassified
See 1 more Smart Citation